The Decision Understanding of Contraception Usage on Fertile Age Couple in Terjun Village - Fitria, Aida (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Total Fertility Rate in North Sumatera is enough high reach until 3 % that indicate increasing of fertility rate. The woman chance for fertilying and boring makes the woman to illness and even the death. So, it is necessary to move up fertile couple age participation more in using contraception for along time. The rate of fertile couple age in Terjun area at 2013 is about 1.863 persons (37,5%). The research to analyze the process of making decision fertile couple age in using contraception. This research used qualitative methode with interpretive paradigama. This research was done in Terjun area District Medan Marelan from January 2013 to April 2014. The informan in this research were the every persons who knows and also take part in using contraception. Such as, fertile couple age (PUS) staff KB in Terjun, friends, and other families. The data collected by interviewing and observation. The real data test by validating test and data realibilty. The result of research showed that in making decision contraception usage, fertile age couple (FAC) consider their decision first by analising some important aspects relate with religion and the efect to their health. The culture in around them, and also economy aspect and accessibilitas of methode. Taking decision for fertile couple age we know that there were three (3) type of decision. The decision of husband-wife with his wife herself to become an acceptor, decision husband wife with her husband himself to be an acceptor, decision husband only with his wife become acceptor. The need for a lot of activities that can empower the public perception that business planning is not a matter forwomenalone. Foritis expected that stake holders such as NGOs (NGO) said that the Board andother relevant agenciesto be more focused and concerned to deal with these problems by providing opportunities for women to acquire good knowledge about contraceptives. The village governmentis also expected to improve access and quality of information, education, counseling and contraceptive services provided to the fertile couples age through the advocacy of health workers who are skilled and friendly. The presence of approaches to religious leaders and community leaders to work together in an effort to increase the use of contraceptionin fertile age couples needs tobe increased again.